PENGARUH KEBERADAAN KOMITE AUDIT DAN AUDIT EKSTERNAL TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA 2016 - 2017 - Nyimas Melia W; Wahyu Meiranto (Diponegoro Journal of Accounting, 2020)
This study aims to examine the influence of audit committees and external auditors such as PwC, Deloitte, KPMG and EY on the quality of earnings management. Size and leverage are used as control variables. The population in this study were all companies listed on the Indonesia Stock Exchange in 2017. The sampling method in this study was purposive sampling. The total number of samples in this study was 233 data, but after going through the data processing stage there were 29 outlier data that had to be excluded from the study sample. Thus, the total number of final samples worth observing is 204 data. Variables of earnings management, audit committee, external audit and interactions between the audit committee and external audit were analyzed by Ordinary Least Square regression The analysis shows that the audit committee and external audit have a significant effect on earnings management. All have a significant negative effect. However, the interaction between the audit committee and external audit has a significant positive effect on earnings management. These results indicate that the two supervisory mechanisms that function together within the company actually show the potential to improve earnings management.